Global phylogeography of the smooth hammerhead shark: Glacial refugia and historical migration patterns - Lopes da Silva Ferrette, Bruno; Coelho, Rui; Peddemors, Victor Marten; Ovenden, Jennifer R.; De Franco, Bruno Alexandre; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Mendonça, Fernando Fernandes (Wiley, 2021)
Extreme climate changes during the Cenozoic Era strengthened different biogeographical barriers that decreased the connectivity among populations, triggering lineage diversification of different species worldwide. The mitochondrial DNA control region was employed to explore the phylogeography of Sphyrna zygaena, a globally distributed species threatened by unsustainable, illegal, unreported and unregulated fisheries triggered by the international shark fin trade. It is listed as ‘Vulnerable’ by the IUCN Red List and its trade is regulated by CITES Appendix II. Only 13 haplotypes were found with low genetic diversity levels (hd = 0.686 ± 0.014; π = 0.00206 ± 0.00004) compared with other species of the Sphyrnidae family. The species has a very strong phylogeographic population structure among the Atlantic, Indian and Pacific Oceans (ΦST = 0.79132). Worldwide, there are six distinct populations with some haplotype sharing. These populations are probably connected by a stepping-stone dispersal of a small number of migrants per generation from the Indo-Pacific towards the Atlantic. Modelling suggests that S. zygaena diverged into two lineages around 6.96 million years ago which have been isolated in glacial refuges in the Atlantic and Indo-Pacific oceans; and after deglaciation, a population expansion probably permitted secondary contact. Conservation plans to establish differentiated management units should be adopted in each of the identified populations. Among these, the Eastern Central Atlantic and West Indo-Pacific are the most important areas for the species considering the historical migration routes that act as a bridge connecting the Atlantic and Indo-Pacific Oceans while the Gulf of Guinea connects the Atlantic populations. Still, further studies are required to know if these populations are also linked with nursery areas for the species. The results herein can help to delimit the main evolutionarily significant units to implement effective policies to establish differentiated management units as starting points to genetic monitoring programmes for Sphyrna zygaena.
Keywords: conservation; delimitation of genetic stocks; fisheries management; historical demography; mitochondrial DNA control region; Sphyrna zygaena; stepping-stone dispersal